ANALYSIS OF THE MAIN INDICATORS OF PASSENGER, FREIGHT AND TRAIN TRANSPORTATION OF THE “J” STATION - Bozorov R.Sh. (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article analyzes the performance of the railway station “J” in terms of freight, passenger and train transportation in recent years. Given the location of the station on high-speed highways, special attention is paid to the issues of ensuring traffic safety of the station’s employees. Currently, one of the pressing issues in railway transport is the problem of soil movement in windy areas, especially in desert areas. It is important to study the negative effects of wind on railway infrastructure and provide scientifically based solutions in this area. For this purpose, the effects of wind on the stability of rolling stock were studied.